An Investigation on the Link between International Labor Migration and Undocumented Employment: Evidence from Turkish Cinema - Hasan Yüksel (Journal of Economy Culture and Society, 2021)
Based upon a Turkish movie named after “Gurbetci Saban (Saban the Expatriate)”, this essay analyzes the portrayal of the link between international labor migration and underground employment within the framework of Turkish immigrants in Germany. Turkish immigration to Germany in a legal context following the Labor Agreement Protocol between Turkey and Germany in October 1961 accelerated in the 1960s and converted into a massive scale thereafter. That agreement was the reflection of the mutual interests of the two states. The reason is that Germany desired to meet its employment needs so as to develop in an industrial way following World War II, which was a real catastrophe for Germans. Meanwhile, in Turkey there was both political and economic upheaval all around the country. Politically, a military coup took place on May 27, 1960 to eliminate Menderes’s Democrat Party and economically, unemployment as well as poverty pushed many to migrate from Turkey. As a matter of fact, this study is the upgraded and new format of its equivalents due to the fact that a qualitative data analysis program called as MAXQDA 2018 was utilized to ascertain Turkish immigrants’ labor market conditions, specifically the underground economy in Germany. Additionally, discourse analysis was used as the research method in the paper.